Digital twins in industrial production and smart manufacturing an understanding of principles, enhancers, and obstacles - Dhanaraj, Rajesh Kumar (IEEE Press, 2024)
Comprehensive reference exploring the benefits and implementation of digital twins in industrial production and manufacturingDigital Twins in Industrial Production and Smart Manufacturing provides an overview of digital twin theoretical concepts, techniques, and recent trends used to meet the requirements and challenges of industrial production and smart manufacturing. The text describes how to achieve industrial excellence through virtual factory simulation and digital modeling innovations for next-generation manufacturing system design.
Keywords: Sonstiges